DEVELOPMENT OF MULTIMEDIA INTERACTIVE SCIENCE LEARNING BASED ON CROSS PLATFORM ON HUMAN REPRODUCTIVE SYSTEM MATERIALS IN THE NINTH GRADE OF JUNIOR HIGH SCHOOL - Guntur Nurcahyanto; Irma Yuliana; Nazzilah Maluha Risalam; Evita Anggraini; Farihatul Faizah Laela (Universitas Lambung Mangkurat, 2024)
This study aimed to develop a multimedia interactive science learning product that is cross-platform-based (handphone and Laptop) with Articulate Storyline 3 Software. The research method used was Research and Development (R&D) with a waterfall process model from Pressman. The data analysis applied to this study consists of quantitative and qualitative data. The research results: 1). Media expert testing obtained an average value of 3.56, with a very decent category; 2). Material expert testing obtained an average value of 3.77, with a very decent category; 3) Limited Scale Test, using usability assessment on students and teachers, obtained an average system usability scale (SUS) value of 75.625, with an excellent category, so it can be concluded that interactive science learning multimedia on human reproductive system material developed is acceptable (proper) used in the process of teaching and learning activities in the ninth grade of junior high school.